2020
DOI: 10.1002/jmv.26213
|View full text |Cite
|
Sign up to set email alerts
|

SARS‐CoV‐2‐reactive interferon‐γ‐producing CD8+ T cells in patients hospitalized with coronavirus disease 2019

Abstract: There is limited information on severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) T‐cell immune responses in patients with coronavirus disease 2019 (COVID‐19). Both CD4+ and CD8+ T cells may be instrumental in resolution of and protection from SARS‐CoV‐2 infection. Here, we tested 25 hospitalized patients either with microbiologically documented COVID‐19 (n = 19) or highly suspected of having the disease (n = 6) for presence of SARS‐CoV‐2‐reactive CD69+ expressing interferon‐γ (IFN‐γ) producing CD8+… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 26 publications
3
63
0
Order By: Relevance
“…Previous studies have not reported the association between IFN-γ and death, even evaluating the COVID-19-reactive CD69+ expressing IFN-γ producing CD8 + T in 25 patients with severe and moderate disease [ 22 ]. Most studies have described the evident immunological dysfunction in the moderate and severe disease, with reduced expression of IFN-γ by CD4 + T, CD8 + T, and NK cells [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have not reported the association between IFN-γ and death, even evaluating the COVID-19-reactive CD69+ expressing IFN-γ producing CD8 + T in 25 patients with severe and moderate disease [ 22 ]. Most studies have described the evident immunological dysfunction in the moderate and severe disease, with reduced expression of IFN-γ by CD4 + T, CD8 + T, and NK cells [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Undiluted tracheal aspirate samples obtained from mechanically ventilated patients were also processed when available. Commercially-available RT-PCR kits were used for SARS-CoV-2 RNA testing, as previously detailed [24].…”
Section: Sars-cov2-2 Rt-pcrmentioning
confidence: 99%
“…Severe acute respiratory syndrome coronavirus 2-specific (SARS-CoV-2-specific) T cell responses have been detected in patients with coronavirus disease 2019 (COVID-19) (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), and while T cell responses against SARS-CoV have been shown to be long lasting (8), it is not yet known whether SARS-CoV-2-specific T cells will confer protection against reinfection. Recent studies have suggested that preexisting T cell immunity to SARS-CoV-2 is present in some unexposed, HDs (6)(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%